2000
DOI: 10.1006/dbio.2000.9709
|View full text |Cite
|
Sign up to set email alerts
|

Periodic increases in elongation rate precede increases in cytosolic Ca2+ during pollen tube growth

Abstract: Pollen tubes grown in vitro require an intracellular tip-high gradient of Ca2+ in order to elongate. Moreover, after about 2 h in vitro both the tip Ca2+ and the elongation rate of lily tubes begin to oscillate regularly with large amplitudes. This raises the question of the phase relation between these two oscillations. Previous studies lacked the temporal resolution to accurately establish this relationship. We have studied these oscillations with a newly developed, high temporal resolution system and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
140
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 33 publications
11
140
3
1
Order By: Relevance
“…Our observation that Ca 21 concentrations increased after growth parallels results obtained with pollen tubes, in which it has even been suggested that pulsatile expansion may actually be divorced from the oscillating Ca 21 gradient (Messerli et al, 2000). To further assess the relationship between Ca 21 and tip growth, we therefore attempted to manipulate cytoplasmic Ca 21 levels while simultaneously monitoring cell expansion.…”
Section: Blocking Ca 21 Entry Leads To Uncontrolled Expansionsupporting
confidence: 75%
See 4 more Smart Citations
“…Our observation that Ca 21 concentrations increased after growth parallels results obtained with pollen tubes, in which it has even been suggested that pulsatile expansion may actually be divorced from the oscillating Ca 21 gradient (Messerli et al, 2000). To further assess the relationship between Ca 21 and tip growth, we therefore attempted to manipulate cytoplasmic Ca 21 levels while simultaneously monitoring cell expansion.…”
Section: Blocking Ca 21 Entry Leads To Uncontrolled Expansionsupporting
confidence: 75%
“…1). Crosscorrelation analysis indicates that the oscillations of the Ca 21 gradient lagged oscillations in growth by 5 s. A similar phenomenon has been observed in pollen tubes, in which the cytosolic Ca 21 increase also lagged growth by 4 s (Messerli et al, 2000;Messerli and Robinson, 2007).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations